ANTIOXIDANT AND ANTIRADICAL ACTIVITY IN VITRO OF HERB EXTRACTS OF SANGUISORBA OFFICINALIS L., GATHERED IN VARIOUS DEVELOPMENT STAGES - Мальцева, Елена Михайловна; Егорова, Наталья Олеговна; Егорова, Ирина Николаевна; Мухамадияров, Ринат Авхадиевич (Medicine in Kuzbass, 2017)
The subject of the investigation. 70 % water-ethanol extracts of Sanguisorba officinalis L. herb. The purpose of the investigation – a comparative research of antioxidant and antiradical activity of 70 % water-ethanol extracts of Sanguisorba officinalis L. herb, gathered during various development stages – beginning of growing, budding, blooming and fruit-bearing, was performed using in vitro methods. Methods of investigation. Antioxidant activity was evaluated by inhibiting lipid peroxidation reaction and adrenalin autoxidation. Antiradical activity of the extracts was determined by the ability to inactivate DPPH-, ABTS-radicals and by their ability to bind nitrogen oxide molecules, inhibiting of superoxide, hydroxyl radical and ions Fe+2chelate activity. Main results. It was determined that herb extracts, gathered during budding and blooming stages, had higher antioxidant and antiradical activity which is explained by high content of polyphenolic compounds, in particular flavonoids in these periods. Scope. The results can be used for creation of new medicinal products from medicinal plants possess antioxidant action. Conclusions. The results of these tests allow to consider Sanguisorba officinalis L. herb, gathered during budding and blooming stages, as perspective antioxidant medicinal herb.